The association between head motion during functional magnetic resonance imaging and executive functioning in older adults - Hanna K. Hausman; Cheshire Hardcastle; Jessica N. Kraft; Nicole D. Evangelista; Emanuel M. Boutzoukas; Andrew O'Shea; Alejandro Albizu; Kailey Langer; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (Neuroimage: Reports, 2022)
Minimizing head motion during functional magnetic resonance imaging (fMRI) is important for maintaining the integrity of neuroimaging data. While there are a variety of techniques to control for head motion, oftentimes, individuals with excessive in-scanner motion are removed from analyses. Movement in the scanner tends to increase with age; however, the cognitive profile of these “high-movers” in older adults has yet to be explored. This study aimed to assess the association between in-scanner head motion (i.e., number of “invalid scans” flagged as motion outliers) and cognitive functioning (e.g., executive functioning, processing speed, and verbal memory performance) in a sample of 282 healthy older adults. Spearman's Rank-Order correlations showed that a higher number of invalid scans was significantly associated with poorer performance on tasks of inhibition and cognitive flexibility and with older age. Since performance in these domains tend to decline as a part of the non-pathological aging process, these findings raise concerns regarding the potential systematic exclusion due to motion of older adults with lower executive functioning in neuroimaging samples. Future research should continue to explore prospective motion correction techniques to better ensure the collection of quality neuroimaging data without excluding informative participants from the sample.